Research progress of diversified health management in improving the quality of life of patients with heart failure (多元化健康管理提高心力衰竭患者生活质量的研究进展) - DING Lizhen (丁利祯) (Journal of International Translational Medicine Limited, 2024)
Chronic heart failure (CHF) refers to the end stage of various heart diseases, and it has become one of the most important issues for modern public health as its high incidence, high admission rate, high mortality rate and consequence of low quality of life. This paper summarized the diversified health management, including quality of life assessment, treatment compliance intervention based on medical-nursing-patient coordination, symptom self-management efficacy, cardiac rehabilitation and extended care, in prevention and treatment of chronic heart failure, and provided reference of improving quality of life of patients with heart failure (慢性心力衰竭(CHF)是指各种心脏基础疾病的终末阶段, 已经成为影响居民健康的重要公共卫生问题, 具有高患病率、高入院率、高病死率、低生活质量等特点。本研究主要总结生活质量评估, 医、护、患协同模式遵医行为干预, 症状自我管理效能, 心脏康复干预措施, 延续护理等多元化的健康管理在CHF患者防治中的应用现状, 旨在为提高CHF患者生活质量提供可参考的价值。)